(untitled) (The Research of Medical Science Review, 2025)
The current study was conducted to investigate Rheumatoid Arthritis in general population aimed to segregate its prevalence in opposite genders and in different age groups of selected demographic origin. The research was conducted using outdoor patients of Rawal Akot laboratories, collecting data from 100 individuals. RA, the most common autoimmune inflammatory arthritis in adults, was assessed for its prevalence in different age groups and genders, with a particular emphasis on diagnostic methods employed in laboratories. Patient reports were analyzed, encompassing key demographic factors such as age, gender, weight, and diagnostic tools. The evaluation revealed a higher prevalence of RA in women compared to men, particularly in individuals aged above 30 and commonly weighing around 60. According to the findings, 73% of female and 27% of male patients experienced the reoccurrence of RA, with the majority of cases observed in individuals aged above 30. The study underscores the importance of addressing prime factors associated with Rheumatoid Arthritis, suggesting that improving the quality of life through a proper diet and incorporating mild exercise or physical activity may contribute to preventing this autoimmune disease. The insights gained from this research have implications for public health initiatives and emphasize the need for targeted interventions aimed at specific demographic groups to mitigate the impact of RA.